Polymerization Efficiency of a Dual-Cured Resin Cement through Zirconia with Three Different Cusp Inclinations - Chang-Yuan Zhang; Hao Yu; Yi-Ling Cheng; Wen-Zhou Wu; Liang-Jun Xu; Hui Cheng (Journal of Spectroscopy)
Assessing the polymerization efficiency of a dual-cured resin cement through zirconia with three different cusp inclinations is the aim of this study. Seventy-two resin cement (Multilink Speed) specimens were light-cured through the zirconia with three different cusp inclinations (30°, 20°, and 0°) for 20 s or 40 s (n=12). For each group, the Vickers hardness (VH) measurement was performed on half of the specimens, whereas the degree of conversion (DC) was tested for the other half with a Fourier transform infrared spectrometer. The recorded data were analyzed with a two-way ANOVA. Varied VH (32.3 ± 3.2–40.3 ± 4.8) and DC (50.5% ± 3.0%–59.6% ± 2.4%) values were obtained from different groups. The cusp inclinations significantly affect the VH (p=0.001) and DC (p<0.001) of the resin cement, and the curing time exhibited a significant effect on the DC (p=0.014) of resin cement but not on the VH (p=0.167). In conclusion, the cusp inclination of zirconia significantly affects the polymerization efficiency of dual-cured resin cement.